2009
DOI: 10.7211/jjsrt.35.448
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seeding exotic pasture grasses on the vegetation recovery of landslide slopes formed by typhoon 9512 in Mikura-jima Island, Izu Islands, Japan

Abstract: 1995 9 12 −1 Castanopsis sieboldii (Makino) Hatusima ex Yamazaki et Mashiba Machilus thunbergii Sieb. et Zucc. Eurya japonica Thunb. Buxus microphylla Sieb. et Zucc. var. japonica (Muell. Arg. ex Miq.) Rehd. et Wils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, the decrease in mean plant density cannot be explained, because the plots were not covered completely by A. sieboldiana; that is, the self-thinning is not expected to be caused by competition between individuals. The Trino-o No.3 landslide slope might be a severe environment for A. sieboldiana, as we observed lodging or slanting of trees in 2007 [1].…”
Section: Growth Of Alnus Sieboldiana Miscanthus Condensatus and Exotmentioning
confidence: 61%
See 4 more Smart Citations
“…However, the decrease in mean plant density cannot be explained, because the plots were not covered completely by A. sieboldiana; that is, the self-thinning is not expected to be caused by competition between individuals. The Trino-o No.3 landslide slope might be a severe environment for A. sieboldiana, as we observed lodging or slanting of trees in 2007 [1].…”
Section: Growth Of Alnus Sieboldiana Miscanthus Condensatus and Exotmentioning
confidence: 61%
“…Analysis of co-variance did not detect significant differences in the regression coefficients between the non-fertilized and fertilized plots. Previously, we reported that individual D0 2 H was greater in fertilized plots than in non-fertilized plots based on data collected from 2004 to 2009 [1], but those differences diminished by 2013. This extended data set indicates that a single fertilization increased individual D0 2 H of A. sieboldiana with effects apparent for several years but diminishing in 10 years.…”
Section: Growth Of Alnus Sieboldiana Miscanthus Condensatus and Exotmentioning
confidence: 89%
See 3 more Smart Citations